Konsep Mahram Jaminan Keamanan atau Pengekangan Perempuan - Atiyatul Ulya (AL-Fikr, 2013)
In accordance with the research, the population of violence among the woman increased dramatically. Therefore, it is strongly required a legal protection to the woman. This article, in this regard, offers a kind of protection that will be called mahram. The main objective of this article is to discuss the meaning of mahram, and to what extend to role of this concept toward the protection of the woman. The writer come to conclude that prophet tradition contains a number of guidance in terms of mahram concept.. This concept entails the model of responsibility in order to build a system so the woman can be active safely among the man.